2023
DOI: 10.1007/s00253-023-12713-y
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Taxol® biosynthesis by endophytic fungi

Kamalraj Subban,
Frank Kempken

Abstract: There have been two hundred reports that endophytic fungi produce Taxol®, but its production yield is often rather low. Although considerable efforts have been made to increase Taxol/taxanes production in fungi by manipulating cocultures, mutagenesis, genome shuffles, and gene overexpression, little is known about the molecular signatures of Taxol biosynthesis and its regulation. It is known that some fungi have orthologs of the Taxol biosynthetic pathway, but the overall architecture of this pathway is unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Despite the fungal fast growth, resistance to mechanical stress, and feasibility of genetic manipulation, the commercial production of Taxol by fungi has been halted by the rapid loss of Taxol productivity with the storage and subculturing [ 14 , 18 , 22 , 59 ]. Thus, screening for a novel endophytic fungal isolate inhabiting the plants of ethnopharmacological uses, could have relatively stable Taxol-producing machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fungal fast growth, resistance to mechanical stress, and feasibility of genetic manipulation, the commercial production of Taxol by fungi has been halted by the rapid loss of Taxol productivity with the storage and subculturing [ 14 , 18 , 22 , 59 ]. Thus, screening for a novel endophytic fungal isolate inhabiting the plants of ethnopharmacological uses, could have relatively stable Taxol-producing machinery.…”
Section: Discussionmentioning
confidence: 99%
“…3 ) 7 , 32 or from cell cultures created from meristematic cells of the yew cambium 7 , 8 , 9 . In principle, it seems that there are no longer any fundamental problems in meeting the demand for this proven anti-cancer drug, although this is sometimes assessed differently 33 , 34 , 35 . Reliable data that would allow the assessment of the coverage of demand are not available.…”
Section: The History Of Taxol As a Drugmentioning
confidence: 99%
“…Also, no published efforts to reproduce the original research results could be observed. It is striking that the seminal publication by Heinig, Scholz, and Jennewein was mostly – and even in broad review articles – ignored 34 , 43 , 44 , 47 , 48 , 61 , 62 , 63 , sometimes dutifully cited, but nevertheless ignored in substance 33 , 44 , 64 . In some cases, the article is correctly summarized in one sentence, but the negative findings have not prompted the researchers to question their own assumptions or, at least, to discuss them in more detail 8 , 45 , 48 .…”
Section: First Doubts Arisementioning
confidence: 99%
“…In 1993, the endophytic fungus Taxomyces andreanae from T. brevifolia was discovered by Stierle et al to produce paclitaxel in vitro [88]. Since then, more and more researchers have been engaged in isolating and characterizing paclitaxel-producing endophytic fungi [89][90][91]. To date, more than 20 genera of endophytic fungi have been identified in Taxus species and non-Taxus species such as sycamore and ginkgo (Table 4) .…”
Section: Paclitaxel-producing Endophytic Fungimentioning
confidence: 99%